Marriage in the city of Hebron between the years (1920-1948) “Using marriage contract records as a primary source” - Abdin , Razan Abd-Alhalim; Al-Shraah, Ibrahim Faour (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to identify the nature of customs and traditions that coincided with matrimony in Hebron’s community during the British presence in Palestine between the years (1920 - 1948), as the marriage contract records in Hebron’s Sharia Court covered this important era of time in the modern history of Palestine. Methods: The approach of this study is primarily based on historical analysis, which dictates examining data from (10,000) marriage contracts gathered in (156) records and analyzing it.The study relies on the contents of these contracts and the official procedures that accompanied them. As it contained fields with vital information, covering names of both spouses, their respective places of residence, amount of dowry, date of the contract, and their respective professions, in addition to the name of the officiant. Furthermore, the matrimony customs of Hebron’s community are tackled. Results:. The study demonstrates the importance of marriage contract records due to the vital information they contain. These records document the nature of family relations within the city of Hebron and whether the marriages took place outside the city, and the currency type used for dowry. Furthermore, the records trace professions occupied within Hebron, which indicated changes imposed by the British Mandate on the city’s community. Conclusions: The study concludes that these records and contracts gave a clear image of social relations within Hebron’s society, given that these contracts were contemporary of the study’s period and were distinguished since they were written and documented by official bodies